2013
DOI: 10.1177/0956797613479387
|View full text |Cite|
|
Sign up to set email alerts
|

The Changing Psychology of Culture From 1800 Through 2000

Abstract: The Google Books Ngram Viewer allows researchers to quantify culture across centuries by searching millions of books. This tool was used to test theory-based predictions about implications of an urbanizing population for the psychology of culture. Adaptation to rural environments prioritizes social obligation and duty, giving to other people, social belonging, religion in everyday life, authority relations, and physical activity. Adaptation to urban environments requires more individualistic and materialistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
392
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 302 publications
(421 citation statements)
references
References 28 publications
20
392
3
6
Order By: Relevance
“…Research has shown that socioeconomic development predicts various indicators of individualism, independence and autonomy, both contemporaneously across nations and historically within nations (Greenfield, 2013;Greenfield, Maynard, & Childs, 2003;Grossmann & Varnum, 2015;Hofstede, 2001;Inglehart & Baker, 2000;H. Park, Twenge, & Greenfield, 2014).…”
Section: Study 2d: Models Of Selfhood In Ecocultural Contextmentioning
confidence: 99%
“…Research has shown that socioeconomic development predicts various indicators of individualism, independence and autonomy, both contemporaneously across nations and historically within nations (Greenfield, 2013;Greenfield, Maynard, & Childs, 2003;Grossmann & Varnum, 2015;Hofstede, 2001;Inglehart & Baker, 2000;H. Park, Twenge, & Greenfield, 2014).…”
Section: Study 2d: Models Of Selfhood In Ecocultural Contextmentioning
confidence: 99%
“…This is not the first paper to draw on the Google Books N-Gram Corpus. Since the seminal publication introducing this resource as well as the new concept of 'culturomics' [13], papers have been published that have analysed patterns of evolution of the usage of different words from a variety of perspectives, such as random fractal theory [14], Zipf's and Heaps' laws and their generalization to two-scaling regimes [15], the evolution of self-organization of word frequencies over time in written English [16], statistical properties of word growth [17,18], socio-historical determinants of word length dynamics [19]; and other studies have been more specifically aimed at issues such as the sociology of changing values resulting from urbanization [20] or changing concepts of happiness [21].…”
Section: Introductionmentioning
confidence: 99%
“…The initial studies carried out on this large database have allowed scholars to address unprecedented questions about language usage. In particular, for the first time it was possible to study quantitatively aspects of cultural change as reflected in language (Michel et al, 2011;Greenfield, 2013), and rigorously assess overall vocabulary drift over the time span of two centuries (Bochkarev et al, 2014). Moreover, methods inspired in statistical mechanics of complex systems were used to study the dynamics of word birth and death (Petersen et al, 2012a), long-range fractal correlations in word frequencies over centuries (Gao et al, 2012), and the scaling behaviour of word frequencies over time as represented by Zipf's (1949) and Heaps' (1978) laws (Petersen et al, 2012b;Gerlach and Altmann, 2013).…”
Section: Introductionmentioning
confidence: 99%